STUDENTS’ PERCEPTION OF ENGLISH LANGUAGE ANXIETY IN SPEAKING SKILL - Sunarya, Novianty; Pitaloka, Finasti (IKIP Siliwangi, 2018)
Abstract Students should learn speaking skill to communicate as one of four major skills in learning English language. However, language anxiety will be experienced by students in learning speaking. The research is aimed to know students’ perception of language anxiety in speaking skill. The learners’ perception of language anxiety deserve a special mention as it is one of the parties directly involved in learning process. This study explores learners’ perceptions of language anxiety in speaking classes at one of the university in Cimahi. This study involved thirty five students from Indonesian Language Department as sample. To collect the data the researchers used numerical likert scale in the questionnaire by Dornyeiand Taguchi (2010: 150) with thirteen questions. From the results, most of students felt the various anxieties when they speak; for example being laugh at by other students when they make mistakes, and most of students feel ashamed if they got bad grades in English. Keywords: Students Perception, Language Anxiety, Speaking.